2007
DOI: 10.1007/s11255-006-9093-6
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic, electrolyte and metabolic changes during percutaneous nephrolithotomy

Abstract: No significant changes occurred in haemodynamics and electrolytes, but there was a trend towards metabolic acidosis. Arterial blood gases should be monitored during and after PCNL in cases with prolonged irrigation time, repeated percutaneous interventions and patients having compromised renal function and metabolic status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 10 publications
0
22
0
3
Order By: Relevance
“…Mohta et al found no significant changes in hemodynamic and electrolytes, but there was a trend towards metabolic acidosis. 30 Atici et al conducted a study to investigate the hormonal and hemodynamic changes during PCNL and concluded that there is a tendency towards hyponatremia and metabolic acidosis, in addition to significant increases in renin, aldosterone and ACTH levels during procedures. 31 Hence arterial blood gases should be monitored during and after PCNL surgeries in cases with prolonged irrigation time, repeated Pleural injury leading to hydrothorax was seen in one case postoperatively which required intercostal chest tube drainage further course of the patient was uneventful.…”
Section: Acidosismentioning
confidence: 99%
“…Mohta et al found no significant changes in hemodynamic and electrolytes, but there was a trend towards metabolic acidosis. 30 Atici et al conducted a study to investigate the hormonal and hemodynamic changes during PCNL and concluded that there is a tendency towards hyponatremia and metabolic acidosis, in addition to significant increases in renin, aldosterone and ACTH levels during procedures. 31 Hence arterial blood gases should be monitored during and after PCNL surgeries in cases with prolonged irrigation time, repeated Pleural injury leading to hydrothorax was seen in one case postoperatively which required intercostal chest tube drainage further course of the patient was uneventful.…”
Section: Acidosismentioning
confidence: 99%
“…Although absorbed fluid was more in the prone group, probably it was not enough to improve hemodynamic imbalance which occurred during the operation. In Mohta and Koroglu's studies there was no significant change in electrolyte levels (Na and K) (3,13). In another study ,it was found that after irrigation by distilled water there was a significant change in Na but not in K (8).…”
Section: Discussionmentioning
confidence: 82%
“…Percutaneous nephrolithotripsy (PCNL) is a common technique to treat kidney stones and is also used to fragment and remove the calyx and pelvic stones (1)(2)(3)(4)(5). Nowadays to manage large stones, stones resistant to fragmentation, or stones with an abnormal anatomy in kidney, PCNL is preferred (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…associated with peri-operative complications especially haemodynamic changes (1), (2) . In a previous study in our department on peri-operative complications of PCNL under general anaesthesia significant haemodynamic changes were noted.…”
Section: Introductionmentioning
confidence: 99%